Mechanisms of Mining Seismicity under Large Scale Exploitation with Multikey Strata - Hu He; Linming Dou; Anye Cao; Jun Fan (Shock and Vibration)
The dynamic disasters are aggravating with the increase of exploitation scale and intensity in Chinese coal mines, to further understand this problem, we studied the mechanisms of mining tremors induced by key strata movement and instability under large scale exploitation. First the mechanisms were categorized into two groups that is main key strata fracture and movement as well as subkey strata instability again under adjacent mining activities. Based on the key strata theory in ground control we revealed three basic mechanisms of key strata destabilization that are rotary and sliding of low subkey strata, shear sliding of the high subkey strata, and the main key strata rupture and cave at limit span, respectively. The microseismic observing systems were applied to monitor the mining tremor events and verify the theoretical analysis in different coal mines. The characteristics of time-space evolution of tremors show that low inferior key strata causing the most, followed by the high inferior key strata and the main key strata least, however the released energy was just opposite.